2015
DOI: 10.1186/s40064-015-1263-5
|View full text |Cite
|
Sign up to set email alerts
|

Survey of aphid population in a yellow passion fruit crop and its relationship on the spread Cowpea aphid-borne mosaic virus in a subtropical region of Brazil

Abstract: BackgroundPassion fruit woodiness may be caused by Cowpea aphid-borne mosaic virus (CABMV) and is currently the major passion fruit disease in Brazil. To assess the virus-vector-host interactions, a newly introduced golden passion fruit plantation located in eastern region of São Paulo State, Brazil, was monitored.MethodsDissemination of CABMV was determined analyzing golden passion fruit plants monthly for 18 months by PTA-ELISA. Seasonality and aphid fauna diversity was determined by identification of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
(39 reference statements)
2
12
0
1
Order By: Relevance
“…This result coincides with the results reported for the ANCOVA analysis, where annual vector pressure index per shoot was found to be a significant co‐variable. This finding agrees with that obtained by Garcêz et al (2015) on Cowpea aphid‐borne mosaic virus (CABMV, Potyvirus) on passion fruit in Brazil. These authors observed that the low abundance and diversity of aphid species did not affect CABMV epidemiology negatively, but described that the presence of efficient vectors such as Aphis fabae and A. gossypii was crucial in the spread of CABMV in passion fruit orchards.…”
Section: Discussionsupporting
confidence: 92%
“…This result coincides with the results reported for the ANCOVA analysis, where annual vector pressure index per shoot was found to be a significant co‐variable. This finding agrees with that obtained by Garcêz et al (2015) on Cowpea aphid‐borne mosaic virus (CABMV, Potyvirus) on passion fruit in Brazil. These authors observed that the low abundance and diversity of aphid species did not affect CABMV epidemiology negatively, but described that the presence of efficient vectors such as Aphis fabae and A. gossypii was crucial in the spread of CABMV in passion fruit orchards.…”
Section: Discussionsupporting
confidence: 92%
“…Management alternatives that are often recommended to reduce the damage caused by CABMV in passion flower include the use of healthy seedlings produced in certified nurseries, the use of seedlings of at least 100–120 cm in height to establish new orchards, the elimination of old and/or infected passion fruit plants before a new planting, disinfection of pruning tools to prevent mechanical transmission of the virus and planting in isolated locations away from known virus sources of inoculum, whenever possible (Fischer & Rezende, ; Cerqueira‐Silva et al , ; Garcêz et al , ). However, these recommendations are not completely effective, and even when they are partially applied, passion flower orchards are renewed annually because of the high rates of infection of plants with CABMV (Cerqueira‐Silva et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit hardening virus, caused by the Cowpea aphid-borne mosaic virus (CABMV) is a species of the genus Potyvirus (Cerqueira- Silva et al, 2014;Rodrigues et al, 2015). It is transmitted by aphids, grafting and mechanically by means of buffered leaf extract and occurs in the main producing areas of Brazil (SILVA et al, 2012;GARCÊZ et al, 2015).…”
Section: Introductionmentioning
confidence: 99%